2023
DOI: 10.1002/agj2.21434
|View full text |Cite
|
Sign up to set email alerts
|

Soybean planting date and seeding rate effect on grain yield and profitability

Fabiano Colet,
Alexander J. Lindsey,
Laura E. Lindsey

Abstract: Timely soybean [Glycine max (L.) Merr.] planting is ideal for maximizing grain yield. However, weather conditions often limit farmers’ ability to plant timely. The objectives of this study were to (a) measure the effect of soybean planting date and seeding rate on grain yield, (b) identify the agronomic optimum soybean seeding rate (AOSR) (the seeding rate where soybean yield is maximized), and (c) compare the net economic return of the base treatment (10 May to 31 May planting date and 370,000 seeds ha−1 seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For example, a seed lot with low germinability will require a higher seeding rate than one with high germinability. Previous research found that planting soybean in late April or early May yields more than later PDs (Colet et al, 2023;Rattalino Edreira et al, 2017); however, there is no study showing the effects of early-planted soybean on seed quality, which is important for seed producers to understand. With the changes in early planting crop insurance dates, soybean can be planted in southern Ohio, Indiana, Illinois, and Iowa as early as April 5 (USDA-RMA, 2023), while soil…”
Section: Implications and Future Workmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, a seed lot with low germinability will require a higher seeding rate than one with high germinability. Previous research found that planting soybean in late April or early May yields more than later PDs (Colet et al, 2023;Rattalino Edreira et al, 2017); however, there is no study showing the effects of early-planted soybean on seed quality, which is important for seed producers to understand. With the changes in early planting crop insurance dates, soybean can be planted in southern Ohio, Indiana, Illinois, and Iowa as early as April 5 (USDA-RMA, 2023), while soil…”
Section: Implications and Future Workmentioning
confidence: 98%
“…Growing degree days (GDDs) were calculated using a base temperature of 10˚C and the average daily temperature for calculation. Additional details regarding these studies can be found in Colet et al (2023).…”
Section: Core Ideasmentioning
confidence: 99%